Pelatihan Bantuan Hidup Dasar pada Palang Merah Remaja (PMR) di SMA Negeri I Kabupaten Deli Serdang - Marlisa; Simangunsong, Dame Evalina (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
Emergencies can happen anytime, to anyone, and anywhere. This condition requires the readiness of health workers and the general public to anticipate this incident. If we look at the deaths due to cardiac arrest and respiratory arrest so far, there have been quite a number of them, especially in the Pre-Hospital area. Helping emergency patients is an effort. The first action is to prevent or protect the victim from the organ function which is very important for the life of the victim, not to provide treatment. Strictly speaking, this is intended to prevent death and avoid disability if the victim's soul can be saved. This community service is based on the results of a 2018 study, which found the effect of providing health education on basic life support on cardiopulmonary resuscitation knowledge in students of SMA Negeri 5 Medan. The results of the research obtained were applied to members of PMR SMA Negeri 1 Percut Sei Tuan Deli Serdang Regency which aimed to improve understanding and skills in the management of shock and basic life support in the school environment and surrounding community. The methods carried out are lectures and demonstrations on the theory and practice of handling shock and basic life support. The implementation of the activity was carried out at SMA Negeri 1 Percut Sei Tuan Deli Serdang Regency, which is a assisted village of the Medan Ministry of Health Poltekkes. Community service activities that have been carried out on 20 members of PMR SMA Negeri I Percut Sei Tuan Deli Serdang Regency, for 3 days, can improve students' understanding and skills about the material provided and the evaluation results show the proficiency of trainees in evacuating victims found in the field.